Kecerdasan Intelektual Pada Tingkat Pemahaman Mahasiswa Akuntansi - Teguh Erawati; Annisa Putri Ambri (Jurnal Ilmiah Wahana Pendidikan, 2023)
The goal of this research was to establish a relationship between intellectual quotient, emotional quotient,accounting knowledge and to examine the moderating role of emotional quotient in the interaction of intellectual quotient. Convenience sampling may be used to choose anywhere from 10-60 samples. The regression analysis revealed that both intellectual quotient and emotional quotient positively impacted accounting knowledge; however, emotional quotient failed to buffer the effect of intellectual quotient.